Analysis of a STEM Based Flipped Classroom Learning Model for Enhancing Metacognition and Student Learning Outcomes in Buffer Solution Topic - Lestari*, Santi Puji; Adhim, Fauzan; Dwi Gita, Rina Sugiarti; Setiawan, Nur Candra Eka (Universitas Syiah Kuala, 2025)
In the current era of globalization, science education requires instructional strategies that not only improve student achievement but also develop metacognitive abilities essential for complex problem solving. However, traditional teaching models are still predominantly used, often limiting students understanding of abstract scientific concepts such as buffer solutions. This study aims to examine the effectiveness of a STEM based flipped classroom model in enhancing students metacognitive skills and learning outcomes. A quasi-experimental design with a pre-test and post-test control group was employed, involving 60 senior high school students divided into experimental and control groups. The instruments used were a learning outcome test and a metacognitive awareness questionnaire, both of which had been validated and proven reliable. The results revealed that students in the experimental group showed significantly higher improvements in both metacognitive awareness and academic performance compared to the control group. These findings suggest that the integration of technology, scientific inquiry, and real world problem solving through a STEM based flipped classroom model positively impacts students conceptual understanding and learning achievements. This study highlights the urgent need for pedagogical transformation in science education and provides evidence supporting the implementation of innovative, technology enhanced learning models to better prepare students for future challenges